Research and development on postharvest management of the Royal Project flowers - D. Boonyakiat (2018)
© 2018 International Society for Horticultural Science. All rights reserved. A survey of postharvest losses of chrysanthemums, roses and hydrangeas starting from the farmers’ field through the arrival at the Royal Project retail shop in Chiang Mai was conducted. The study compared the postharvest losses of each flowering plant before and after improving the postharvest handling process. For chrysanthemums, the postharvest survey of the three cultivars, namely, ‘Celebrate’, ‘Orange Day’, and ‘Campus’ was conducted. In case of roses, comparison of the three cultivars, ‘Persia’, ‘Twilight’ and ‘Cantaloupe’ was conducted, while the study of hydrangea explored the three cultivars ‘Blue Color No. 031’, ‘White Color No. 027’, and the ‘Old Blue Color’. The vase life of the chrysanthemum cultivars including ‘Celebrate’, ‘Orange Day’, and ‘Campus’ before improving the process was 10.1, 10.5 and 9.4 days, while the improved postharvest handling prolonged the vase life to 14.2, 14.7 and. 18.7 days, respectively. For the rose cultivars, ‘Persia’ had a regular vase life of 4.32 days before the postharvest handling was improved. With the developed handling process, the vase life for ‘Persia’ roses was extended to 7.7 days for dry transport and 8.5 days for wet transport. For ‘Twilight’ roses, the vase life was prolonged to 10.9 days and 11.2 days for flowers in dry transport and wet transport, respectively, from the normal vase life of only 3.8 days. Similarly, ‘Cantaloupe’ roses’ vase life in dry and wet transport was extended to 8.0 and 8.4 days, respectively, as opposed to the normal life of 3.7 days before the postharvest handling was improved. Likewise, the improved postharvest handling for hydrangeas ‘Blue Color No. 031’ lengthened the vase life to 6.9 days and 7.3 days for those in a vase containing distilled water and in a vase with a solution of citric acid with a pH of 4, respectively, as compared to 3.07 days with traditional postharvest handling. The vase life of the hydrangea ‘White Color No. 027’ in a vase with distilled water, and a vase with a solution of citric acid with a pH of 3 was extended to 2.9 days and 5.1 days, respectively, while the traditional handling process could only maintain 1.8 days vase life. In case of hydrangea ‘Old Blue Color’, the vase life with customary postharvest handling was 3.5 days. The developed process extended the vase life for flowers in a vase containing distilled water and the one filled with a solution of citric acid with a pH of 4 to 6.5 and 5.8 days, respectively.